Transcranial Color‐Coded Duplex in Acute Encephalitis: Current Status and Future Prospects. Issue 4 (12th May 2016) - Kargiotis, Odysseas; Safouris, Apostolos; Magoufis, Georgios; Stamboulis, Eleftherios; Tsivgoulis, Georgios
ABSTRACT: BACKGROUP AND PURPOSE: There are limited data regarding the diagnostic yield of transcranial color‐coded Doppler (TCCD) in acute encephalitis. We present our preliminary observations of consecutive ultrasound evaluations in 2 patients with acute encephalitis and we review the possible diagnostic role of TCCD in such cases. METHODS: We describe two cases of acute encephalitis that presented with aphasia and confusion and underwent repeat TCCD evaluation at baseline and after 48 hours in both patients. We also critically review the current literature regarding potential TCCD applications in acute central nervous system infections. RESULTS: Serial TCCD evaluations revealed the following triad of abnormal findings in both patients: (i) elevated pulsatility index (PI) in the left middle cerebral artery (M1 MCA) at baseline (>1.2), (ii) increased PI in left M1 MCA by >25% in comparison to right M1 MCA, and (iii) decrease in PI in left M1 MCA by >25% at the follow‐up evaluation at 48 hours. The decrease in PI in left M1 MCA coincided with symptom improvement in both patients. DISCUSSION: The focal transient increase in left M1 MCA PI may be attributed to focally increased intracranial pressure or peripheral vasospasm of distal left MCA branches. Since there are limited reports in the literature concerning TCCD evaluation of patients with central nervous system infections, our preliminary findings require independent confirmation in a larger series of patients.